Resveratrol relieves hypoxia-reoxygenation-induced mitophagy in TCMK1 cells - JIANG Luo-jia, XU Hai-bo (Jichu yixue yu linchuang, 2022)
Objective To study the effect of resveratrol (Res) on mitochondrial function and mitophagy in mouse renal tubular epithelial cell line TCMK1 induced by hypoxia-reoxygenation (H/R). Methods The H/R model cell was established in vitro, and TMCK1 cells were pre-treated with Res or (and) mitophagy inhibitor 1 (Mdivi-1) for 2 h. CCK-8 method was used to measure cell viability. Flow cytometry was applied to determine cell mitochondrial membrane potential(MMP) and reactive oxygen species(ROS). Western blot was adapted for determining the protein expression levels of optic atrophy (OPA), dynamin-related protein(DRP) and cleaved caspase-3. Cellular immunofluorescence was used to observe the co-localization of mitochondrial outer membrane translocase (TOMM20) and autophagolysosome-associated membrane protein 2 (LAMP2). Results There was significantly reduction in the survival rate of TCMK1 cells in H/R group versus control (P＜0.05). The intracellular calcium ion, ROS and MMP contents were significantly reduced (P＜0.05), and the expression of OPA was significantly reduced(P＜0.05). The expression of DRP was significantly improved (P＜0.05), and the number of mitochondria and LAMP2 co-localized significantly decreased. As compared to the H/R group, 10 μmol/L Res could significantly increase the survival rate of TMCK1 cells (P＜0.05), and inhibit the release of ROS, calcium overload and the decrease of MMP in TCMK1 cells after H/R injury (P＜0.05). While Res could promote the expression of OPA and inhibite the expression of DRP (P＜0.05), increase the number of cells with co-localized mitochondria and LAMP2. Compared with (HR+Res) group, the expression of cleaved caspase-3 and Bax increased, while the expression of Bcl2 decreased after Mdivi-1 was administered on the basis (P＜0.05). Conclusions Res attenuation of H/R-induced TCMK1 cell damage is medicated at leaet in part by activation of mitophagy and maintaining mitochondrial dynamic homeostasis as one of potential mechanisms.